Improving Adoptive T Cell Therapy: The Particular Role of T Cell Costimulation, Cytokines, and Post-Transfer Vaccination - Redeker, Anke; Arens, Ramon (Frontiers in Immunology, 2016)
Adoptive cellular therapy (ACT) is a form of immunotherapy whereby antigen-specific T cells are isolated or engineered, expanded ex vivo and transferred back to patients. Clinical benefit after ACT has been obtained in treatment of infection, various hematological malignancies and some solid tumors, however, due to poor functionality and persistence of the transferred T cells, the efficacy of ACT in the treatment of most solid tumors is often marginal. Hence, much effort is undertaken to improve T cell function and persistence in ACT and significant progress is being made. Herein we will review strategies to improve ACT success rates in the treatment of cancer and infection. We will deliberate on the most favourable phenotype for the tumor-specific T cells that are infused into patients and on how to obtain T cells bearing this phenotype by applying novel ex vivo culture methods. Moreover, we will discuss T cell function and persistence after transfer into patients and how these factors can be manipulated by means of providing costimulatory signals, cytokines, blocking antibodies to inhibitory molecules and vaccination. Incorporation of these T cell stimulation strategies and combinations of the different treatment modalities are likely to improve clinical response rates further.